Management of Proptosis in a Case of Sphenoid-Orbital Meningioma - Rahman, Md Moshiur; Khan, Robert Ahmed; Khan, SIM Khairun Nabi; Arifin, Mohammad Samsul; Chowdhury, Muhtamim (Bangladesh Journal of Neurosurgery, 2022)
Sphenoid-orbital meningiomas (SOMs) are difficult to completely resect because they involve the sphenoid wing, orbit, and cavernous sinus. As the tumor invades the optic canal, SOMs frequently appear with visual deficits. The authors of this case report dealt with the case of a 65-year-old male patient who had right-sided proptosis. We diagnosed the patient, and his MRI revealed of having SOMs. The surgical approach was determined by the tumor’s placement in the orbit and cranial cavity and its connections to the optic canal and optic nerve axis. Surgical excision was used to successfully remove the SOM. The patient maintained a proptosis of less than 4 mm during the follow-up period. The visual acuity, visual field, and ocular fundus were examined during the optical follow-up. SOMs are notoriously difficult to treat surgically. The primary goal of surgery in symptomatic individuals with SOMs is to slow down the tumor’s progression. Longer periods of post-operative observation and follow-up are recommended to observe long-term advantages. Bang. J Neurosurgery 2022; 11(2): 145-149